Presence of anti-microbial antibodies in liver cirrhosis--a tell-tale sign of compromised immunity? - Maria Papp; Gary L Norman; Zsuzsanna Vitalis; Istvan Tornai; Istvan Altorjay; Ildiko Foldi; Miklos Udvardy; Zakera Shums; Tamas Dinya; Peter Orosz; Bela Lombay; Gabriella Par; et al. (PLoS ONE, 2010)
BACKGROUND: Bacterial translocation plays important role in the complications of liver cirrhosis. Antibody formation against various microbial antigens is common in Crohn's disease and considered to be caused by sustained exposure to gut microflora constituents. We hypothesized that anti-microbial antibodies are present in patients with liver cirrhosis and may be associated with the development of bacterial infections. METHODOLOGY/PRINCIPAL FINDINGS: Sera of 676 patients with various chronic liver diseases (autoimmune diseases: 266, viral hepatitis C: 124, and liver cirrhosis of different etiology: 286) and 100 controls were assayed for antibodies to Saccharomyces cerevisiae (ASCA) and to antigens derived from two intestinal bacterial isolates (one gram positive, one gram negative, neither is Escherichia coli). In patients with liver cirrhosis, we also prospectively recorded the development of severe episodes of bacterial infection. ASCA and anti-OMP Plus™ antibodies were present in 38.5% and 62.6% of patients with cirrhosis and in 16% and 20% of controls, respectively (p<0.001). Occurrence of these antibodies was more frequent in cases of advanced cirrhosis (according to Child-Pugh and MELD score; p<0.001) or in the presence of ascites (p<0.001). During the median follow-up of 425 days, 81 patients (28.3%) presented with severe bacterial infections. Anti-microbial antibody titers (p = 0.003), as well as multiple seroreactivity (p = 0.036), was associated with infectious events. In logistic regression analysis, the presence of ascites (OR: 1.62, 95%CI: 1.16-2.25), co-morbidities (OR: 2.22, 95%CI: 1.27-3.86), and ASCA positivity (OR: 1.59, 95%CI: 1.07-2.36) were independent risk factors for severe infections. A shorter time period until the first infection was associated with the presence of ASCA (p = 0.03) and multiple seropositivity (p = 0.037) by Kaplan-Meier analysis, and with Child-Pugh stage (p = 0.018, OR: 1.85) and co-morbidities (p<0.001, OR: 2.02) by Cox-regression analysis. CONCLUSIONS/SIGNIFICANCE: The present study suggests that systemic reactivity to microbial components reflects compromised mucosal immunity in patients with liver cirrhosis, further supporting the possible role of bacterial translocation in the formation of anti-microbial antibodies.